Analisis Paid Promote dan Endorsement Pada Penjualan Online Produk Pegadaian PT Pegadaian CP Kentungan Analysis of Paid Promote and Endorsment on Online Sales of Pegadaian Product at PT Pegadaian CP Kentungan - Panganton, Chintia; Triana, Dewi (EBBANK, 2025)
This study explores the effectiveness of paid promote and endorsement strategies in enhancing online sales at PT Pegadaian CP Kentungan. Employing a descriptive qualitative method with a case study approach, data was collected through in-depth interviews, direct observations, and documentation. The results reveal that paid promote is effective in broadening promotional reach through social media accounts aligned with target audiences, while endorsement improves brand trust and consumer credibility through influencer engagement. These strategies complement one another by increasing digital interactions and fostering consumer interest, thus proving to be valuable for enhancing online marketing in financial institutions.